IMPLEMENTATION OF ACADEMIC SUPERVISION ON DIFFERENTIATED LEARNING IN PUBLIC SD 07 SUNGAI RAYA KUBU RAYA DISTRICT - Rohayati, Rohayati (Jurnal Pendidikan Sosiologi dan Humaniora, 2023)
The aim of the research is to describe the implementation of differentiated learning through academic supervision at SD Negeri 07 Sungai Raya. The research subjects were grade 1 teachers and grade IV teachers who implemented the Merdeka curriculum using differentiated learning. The method used is descriptive qualitative. The data analysis used is qualitative analysis. Research data shows that the implementation of differentiated learning through academic supervision at SD Negeri 07 Sungai Raya has been carried out in accordance with planning, implementation and supervision results. This is demonstrated by the plans prepared by the teacher. The implementation of differentiated learning that has been carried out by teachers through academic supervision has been carried out. Teachers have prepared the implementation of learning that will be carried out properly. Academic supervision is, carried out to help teachers improve their professional abilities, which include academic knowledge, classroom management, and learning process skills, and can use all these abilities to provide quality learning experiences for students